Pelatihan Penerapan Metode Pencocokan Kartu Indeks untuk Meningkatkan Keterampilan Mendengar Bahasa Inggris Siswa Sekolah Menengah Atas - Sudewi, Putu Wahyu; Putri, Andi Mega Januarti; Amrang, Amrang (Jurnal Pengabdian UNDIKMA, 2024)
This community engagement activity aims to enhance high school students’ English listening skills through the application of the index card matching method. The implementation method of this service involved training that includes preparation, implementation, practice, and evaluation stages. The participants of this training were 34 students from class XII in SMAN 1 Wonomulyo, Polewali Mandar Regency. The evaluation instrument for this activity used a pre-test and post-test with quantitative data analysis. The results of this community service activity showed an improvement in students’ listening skills after applying the index card matching method. The average student score increased by 34 points from the initial test average score of 46.00 to 80.00 on the final test. During the community service process, students showed interest and a positive response, and actively participated in the learning process with high enthusiasm and interaction.